Teachers Perception towards Problem of Learning Social Studies among Students at Upper Primary Schools nearby Slum area in Maharashtra - Sethy, Dr. Premananda; Deep, Dr. Sambhu Sankar (Voices of Teachers and Teacher Educators, 2020)
This paper focuses on teachers’ perception towards the problems of learning social studies among students from slums and children of socio-economically backward parents at upper primary level. It analyses the perception through interview of social studies teachers (SST) teaching in schools near a pre-dominantly slum area of Mumbai Urban and Suburban district of Maharashtra State. The paper also highlights problems faced by teachers in pedagogical processes and explores their reflective practices and their attempts to improve the process of teaching and learning in the classroom. The data collected through different sources have been triangulated to understand the problems of learning social studies through thematic analysis of responses on different characteristics of sample schools. It is suggested that all SSTs should be reflective practitioners and improve the quality of education through action research and solve the immediate problems of teaching and learning social studies inside the classroom. Evidence has been derived from the transcription of teacher interview to reflect on the way of teaching and learning and develop the skill of creative thinking and critical thinking among learners through the activity-based learning.